Богатырские русские сказки - Егунов И. (Волшебные сказки и легенды, 2005)
Экземпляры: аб. (2006) / Инвентарный номер: 49949 / Цена: / Сис.шифр: 82.3(2Рос=Рус)-6 / Авт.знак: Б 73 / ГРНТИ: 17.71.91 / ББК: 82.3(2Рос=Рус)-6